Risk factors for adult‐onset recurrent respiratory papillomatosis. (10th June 2014) - Ruiz, Ryan; Achlatis, Stratos; Verma, Avanti; Born, Hayley; Kapadia, Farzana; Fang, Yixin; Pitman, Michael; Sulica, Lucian; Branski, Ryan C.; Amin, Milan R.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To evaluate risk factors strongly associated with adult‐onset recurrent respiratory papillomatosis (AO‐RRP). Study Design Prospective, age‐ and sex‐matched, case control. Methods Patients with AO‐RRP and controls completed a computer‐based, 89‐item questionnaire across three academic institutions. Results Forty‐eight AO‐RRP patients were compared to 73 controls; 43 of the 48 AO‐RRP patients were male (89.5%). The difference in the median number of lifetime sexual partners between AO‐RRP (15) and controls (10) was significant (P = 0.0387). Additionally, an increased number of lifetime sexual partners (≥ 26) was associated with AO‐RRP. No significant difference for the number of lifetime oral sex partners was observed between groups. Increased comorbidity, as quantified by the Charlson Comorbidity Index, was observed in patients with AO‐RRP. AO‐RRP and control groups were similar across many other variables, including birth history, smoking history, alcohol use, drug use, education, income, and the Short Form Health Survey scores. Conclusions AO‐RRP was not associated with previously proposed risk factors for juvenile‐onset RRP and may be associated with an increased number of lifetime sexual partners. Level of Evidence 3b. Laryngoscope 124:2338–2344, 2014